PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA DOSEN DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING (STUDI EMPIRIS DI STMIK â€œAUBâ€ SURAKARTA, JAWA TENGAH) - Wardhana, Galih Wisnu; Choerudin, Achmad (-)
The purpose of the research were to examine the influence of leadership, and discipline to performance of Lecturer of STMIK "AUB" Surakarta with a motivation as intervening variable. The hypothesis which have been formulated in this research show that the leadership, and discipline have influenced the performance of the Lecturers of STMIK "AUB" Surakarta with motivation as intervening variable. The research is a survey to Lecturers of STMIK "AUB" Surakarta. Sample in this researh are 42 respondents. Data have been collected with quesionare processed with, validity and reliability test, the path analysis, t test, F test and test of R2 . The t test result show that leadership, and discipline have positive and significant influence to performance of Lecturer STMIK "AUB" Surakarta partial, motivation has negative and significant influence to performance partially. The F test shows that the leadership, discipline and motivation significant influence toward performance of lecturers STMIK "AUB" Surakarta as simultanoursly. From test of R2 show the independent variable (leadership, discipline, and motivation) explain the dependent variable (performance) and the remaining 99% of 1% is explained by other variables not included in the regression model. The results of path analysis shows that the motivation did not intervern the leadership, discipline, to performance because the value of the coefficient of the indirect effect was smaller than the direct effect. Keywords: leadership, discipline, motivation and performance